The reality-based rules of the workplace : know what boosts your value, kills your chances, & will make you happier - Wakeman, Cy (Recorded Books, Inc., 2020)
For many, work has never seemed harder. In tough economic times, and the aftermath of hiring freezes and layoffs, people are asked to do the same amount of work with reduced resources, sometimes even for reduced benefits and pay. Many employees feel unrecognized and under-rewarded, with studies showing workplace dissatisfaction at record highs. But what if the things that are currently making you unhappy simply lost their power over you? What if you could go to work feeling energetic and excited, regardless of any external circumstances? What does it take to be valued, appreciatedeven a favorite at the office? More than anything else, your satisfaction and success at work depend on understanding exactly how you are evaluated, and your annual performance review doesnt tell the whole story. The Reality-Based Rules of the Workplace goes beyond guesswork to reveal a formula for understanding how your manager calculates your value to the organization. Based on her research with more than 50,000 people, Cy Wakeman reveals a formula for measuring your current performance, your future potential, and your emotional expensethe toll your actions and attitudes take on the people around you, which is your single biggest detractor. Only once you know your true score can you improve it. With Cys clear, straight-to-the-point advice, you can quickly boost your value to your manager and colleagues. You will become an invaluable team member, and even learn to love your job again. Building on the revolutionary lessons of Reality-Based Leadership, Cys first book for leaders and managers, this new book shares practical, real-world advice for how anyone can quickly become a highly valued, sought-after employee and teammate. The Reality-Based Rules of the Workplace is the essential guide for boosting your value, owning your career, and becoming the kind of employee no organization can afford to lose.